2015
DOI: 10.1007/s00774-015-0725-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the lean mass index and bone mass and reference values of muscular status in healthy Chinese children and adolescents

Abstract: This study aimed to analyze the relationships between the lean mass index (LMI) and bone outcomes in Chinese children and adolescents using dual-energy X-ray absorptiometry (DXA) and to establish sex-specific reference percentile curves for the assessment of muscle status. A total of 1541 Chinese children and adolescents between the ages of 5 and 19 years were recruited from southern China. Body composition was measured by DXA (Lunar Prodigy) to acquire total body and total body less head (TBLH) measures. LMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 43 publications
3
26
1
1
Order By: Relevance
“…Despite finding similar patterns of lean mass quantity during adolescence to already established norms, comparisons with previously published data indicate substantial populational variability in lean mass. Our studied population from Southern Brazil exhibited greater lean mass (absolute and adjusted values) for each age group within sexes than adolescents from China [13], Thailand [19] and the United States [25] (exception for 16 years-old-boys and 15 years-old-girls); all studies used the same body composition technique (i.e. DXA).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite finding similar patterns of lean mass quantity during adolescence to already established norms, comparisons with previously published data indicate substantial populational variability in lean mass. Our studied population from Southern Brazil exhibited greater lean mass (absolute and adjusted values) for each age group within sexes than adolescents from China [13], Thailand [19] and the United States [25] (exception for 16 years-old-boys and 15 years-old-girls); all studies used the same body composition technique (i.e. DXA).…”
Section: Discussionmentioning
confidence: 97%
“…Emerging research has quantified lean mass in the pediatric population for the development of lean mass reference curves using dual energy x-ray absorptiometry (DXA), a reference body composition technique that is relatively simple and of minimal burden to the individual [8,9]. Studies conducted in several countries including the United States [10], Canada [11], UK [12], China [13], India [14], and Korea [2] employed the DXA technique, providing reference data for lean mass in children and adolescents. A similar pattern of lean mass accrual was seen across studies; although lean mass increased with age in both sexes, boys had a greater accretion of this body compartment than girls.…”
Section: Introductionmentioning
confidence: 99%
“…Since the correlation of body composition measurements, as well as of BMD measurements using different Lunar machines has been found to be strong [33], we used the raw data without adjustment for the apparatus used. We calculated the appendicular SMI as the sum of the arms and legs lean soft tissue mass divided by the height squared (kg/m 2 ), which is known to be a good estimate of the total body skeletal muscle mass [17]. Fat mass was calculated as the fat mass percentage (fat %) of the total body weight.…”
Section: Data Collection and Measurementsmentioning
confidence: 99%
“…However, lean soft tissue mass includes not only skeletal muscles but also all soft tissues, with the exception of fat mass [15]. Even though total-body lean soft tissue mass correlates with BMD in adults [16], skeletal muscle index (SMI), which is calculated as the lean soft tissue mass weight (kg) of the arms and legs divided by the height squared (m 2 ), is considered to be a more accurate estimate of skeletal muscle mass [15], and consequently correlates better with BMD [17]. To our knowledge, there are no reported data on SMI or on the association between SMI and BMD in young adults with childhood-onset IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as the skeletal muscle mass is the dominant tissue in arms and legs, recently it has been suggested to use DXA-derived appendicular LM as a measure of skeletal muscularity. In this respect, it has been shown that total body BMC was highly correlated with total body lean mass index (LMI) and appendicular LMI in non-athletic boys and girls 25 . In girls, LM is independently associated with bone mass explaining 67% of the total variance in whole-body BMC 16 .…”
mentioning
confidence: 99%